Implementasi Lean Canvas Pada Project Corporate Entrepreneurship - Eric Harianto (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2018)
The purpose of this research is to (1) identify project corporate entrepreneurship with the application of lean canvas; (2) identify constraints in the application of lean canvas in corporate entrepreneurship projects; (3) identify the benefits contained in the application of lean canvas in corporate entrepreneurship projects. Data is collected from October 2018 to December 2018. The method used is descriptive research method with qualitative approach. The researcher conducted interviews with 5 informants. The analysis tools used are lean start up and lean canvas. The data analysis techniques used is Creswell data analysis techniques (2014). The results of this study are (1) project corporate entrepreneurship can be implemented in nine lean canvas blocks and can easily see the concept of optimization model and linkages between nine blocks in lean canvas; (2) the most difficult constraints experienced are when filling key metric blocks and unfair advantages in the lean canvas; (3) the researcher can easily analyze project corporate entrepreneurship in determining future strategies in order to find out which projects are effective or not to be continued or developed based on the achievement measured in the key metric blocks in one of the lean canvas blocks and the integration of nine blocks in lean canvas.